Estudo sobre os Fatores de Sucesso de Startups de Software sob a Perspectiva Empreendedora - de Godoi, Tatiany Xavier; Menolli, André; Dionísio, Gustavo Marcelino (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Entrepreneurship, innovation and startup are widely used terms lately, and much information is currently available on this subject. Software startups are companies that have particular characteristics, such as being scalable, developing innovative products, and living in an environment of uncertainty. Considering the scenario of these types of companies is still incipient, this paper aims to analyze the perception of software startups in relation to the main factors described in the literature that can lead to success or failure. For that, a survey was carried out with software startups incubated in Paraná. The results show that the startups perception is that their success is related only to internal factors of the company, and that many software startups are not prepared as they should in the early stages of development, not applying several concepts described in the literature as fundamental to aid in the business development and validation.